Tumor grade as significant prognostic factor in pancreatic cancer: validation of a novel TNMG staging system - Hlavsa, J; Cecka, F; Zaruba, P; Zajak, J; Gurlich, R; Strnad, R; Pavlik, T; Kala, Z; Lovecek, M (Neoplasma, 2018)
Aim of the study was to asses the tumor grade prognostic value in the Czech pancreatic cancer patients and to evaluate the accuracy of TNMG prognostic model. Retrospective analysis of 431 pancreatic cancer patients undergoing pancreatic resection in seven Czech oncological centers between 2003 and 2013 was performed. The impact of tumor grade and the accuracy of TNMG prognostic model were evaluated. Lymph node status, tumor size, tumor stage and grade were proved as statistically significant survival predictors. The lower tumor differentiation (grade 3 and 4) was associated with poorer prognosis in all stages (stage I: HR 2.23 [1.14; 4.36, CI 95%] p=0.019, stage II: HR 3.09 [2.01; 4.77, CI 95%] p=0.001, stage III and IV: HR 3.52 [1.73; 7.18, CI 95%] p=0.001). Kaplan-Meier analysis verified statistically significant impact of new TNMG stages on survival after resection for pancreatic cancer (p=0.001). In conclusion, we can state that the tumor grade was confirmed as statistically significant prognostic factor in pancreatic cancer. Its incorporation into the current TNM classification enables more accurate prognosis prediction within particular clinical stages. That is why an inclusion of the grade to the standard TNM classification should be discussed.
Keywords: pancreatic cancer; grade; retrospektivní studie; Kaplan-Meier Estimate; Neoplasm Grading; staging nádorů; nádory slinivky břišní; Humans; Kaplanův-Meierův odhad; Neoplasm Staging; TNM classification prognosis.; lidé; Pancreatic Neoplasms; Retrospective Studies; Prognosis; prognóza; stupeň nádoru